Diversity, equity, and inclusion in higher education: an examination of the lived experiences of African American board of trustees within community colleges - Smalls, Carl Bernard (Kansas State University, 2023)
This qualitative narrative inquiry study explored the lived experiences of African American boards of trustees within community colleges around race, barriers, and influencers. Research reveals an underrepresentation of racial diversity among community college boards of trustees that fails to emulate the racial and ethnic diversity of their community college students. Historically and currently, the majority of the board of trustees in American community colleges are older white males. An analysis of the research shows negligible progress in diversifying minority-serving community college boards of trustees, which has created a need to understand what has led to this underrepresentation of minority community college boards of trustees. The qualitative study applied Critical Race Theory (CRT), Critical Race Theory in Education (CRTE), and the Theory of Representative Bureaucracy (TRB) as its theoretical frameworks and lens respectively to conduct the proposed research. An illustrative sample of African American boards of trustees representing diverse backgrounds within community colleges across several states and regions in the United States participated in the study. The participants in the study provided insight into their lived experiences of being a board of trustee member. The study consisted of semi-structured interviews. The trustees described their perceptions of the underrepresentation of African Americans among the board of trustees at community college, their appointment or election to the board of trustees, and the preparation necessary to become a board of trustee member at a community college. Additionally, the study was designed to make a practical, theoretical, and social contribution to the study of the underrepresentation of race in the community college board of trustees, and discuss implications for future research and practice.
Keywords: Minority community college board of trustees; Critical race theory; Critical race theory in education; Systemic biases and racism; Race; African Americans